Ventricular Tachycardia: A Rare Commotio Cordis Presentation. Issue 2 (February 2017) - Jones, Landon A.; Sullivan, Ross W.
Abstract : Abstract: Commotio cordis is a rare event caused by an unfortunately timed blunt anterior chest wall impact that most commonly presents in young male adolescents and is the second leading cause of death in young athletes. The most common initial presenting dysrhythmias are ventricular fibrillation and asystole, although other rare dysrhythmias have been reported—predominantly in animal models. To our knowledge, this is the first telemetry-confirmed case of commotio cordis with a presenting cardiac rhythm of ventricular tachycardia. While prompt recognition of commotio cordis and early cardiopulmonary resuscitation and defibrillation (if applicable) are still the treatment in these cases, our case offers potential insight into the underlying commotio cordis process.